Comparison of the Optical Properties of Graphene and Alkyl-terminated Si and Ge Quantum Dots. Issue 1 (December 2017) - Weerd, Chris; Shin, Yonghun; Marino, Emanuele; Kim, Joosung; Lee, Hyoyoung; Saeed, Saba; Gregorkiewicz, Tom
Abstract Semiconductor quantum dots are widely investigated due to their size dependent energy structure. In particular, colloidal quantum dots represent a promising nanomaterial for optoelectronic devices, such as photodetectors and solar cells, but also luminescent markers for biotechnology, among other applications. Ideal materials for these applications should feature efficient radiative recombination and absorption transitions, altogether with spectral tunability over a wide range. Group IV semiconductor quantum dots can fulfill these requirements and serve as an alternative to the commonly used direct bandgap materials containing toxic and/or rare elements. Here, we present optical properties of butyl-terminated Si and Ge quantum dots and compare them to those of graphene quantum dots, finding them remarkably similar. We investigate their time-resolved photoluminescence emission as well as the photoluminescence excitation and linear absorption spectra. We contemplate that their emission characteristics indicate a (semi-) resonant activation of the emitting channel; the photoluminescence excitation shows characteristics similar to those of a molecule. The optical density is consistent with band-to-band absorption processes originating from core-related states. Hence, these observations strongly indicate a different microscopic origin for absorption and radiative recombination in the three investigated quantum dot systems.